Satpol PP Dan Penanganan Bencana: Studi Kasus Kolaborasi Penegakan Ketertiban Dan Kesiapsiagaan Di Kabupaten Sumedang - Ghany Kusuma Wardhani; Sapto Pramono; Zainal Fatah; Ika Devy Pramudiana (Journal of Innovative and Creativity, 2025)
Disaster management in areas prone to landslides requires planned and structured cooperation between various parties, including involving Satpol PP as an enforcement agency. This study aims to analyze the strategic function of Satpol PP in supporting disaster preparedness and management in Sumedang Regency, especially through collaboration with BPBD, TNI/Polri, village officials, and volunteers. The approach used is qualitative with a case study design, data collection through in-depth interviews, observation of evacuation simulation activities, and analysis of policy documents and disaster management reports during the period January–April 2025. The research findings indicate that the presence of Satpol PP not only contributes to the control of landslide-prone areas and securing evacuation routes, but also increases public compliance with development regulations in dangerous zones, as seen from the reduced number of violations. Collaboration between sectors has been shown to speed up the evacuation process during simulations and reduce the potential risk of loss of life. However, this study also identified challenges such as a lack of trained experts, suboptimal division of roles, and spatial data on vulnerable areas that have not been well integrated. The study's conclusion emphasizes the need to strengthen a more structured collaboration model, expand disaster training for Satpol PP personnel, and update disaster management regulations to be more responsive and flexible. It is recommended that local governments form inter-sectoral forums that actively involve Satpol PP in planning, implementing, and evaluating disaster risk reduction policies in landslide-prone areas.